\( 2 x^{2}+x+3=0 \) The solution set is \( \} \). Use the quadratic formula to solve the equation. (Type an exact answer, using radicals as needed. Use a comma to separate answers as needed.)
Real Tutor Solution
Answer
Solution
Sign in to Unlock Answers for Free!
A Learning Platform Trusted by Millions of Real Students and Teachers.
Reviewed and approved by the UpStudy tutoring team
Bonus Knowledge
To solve the quadratic equation \( 2x^{2}+x+3=0 \) using the quadratic formula \( x = \frac{-b \pm \sqrt{b^2-4ac}}{2a} \), we first identify the coefficients: \( a = 2 \), \( b = 1 \), and \( c = 3 \). Calculate the discriminant: \[ b^2 - 4ac = 1^2 - 4(2)(3) = 1 - 24 = -23 \] Since the discriminant is negative, the solutions will be complex. Now apply the quadratic formula: \[ x = \frac{-1 \pm \sqrt{-23}}{2(2)} = \frac{-1 \pm i\sqrt{23}}{4} \] Thus, the solution set is: \[ \left\{ \frac{-1 + i\sqrt{23}}{4}, \frac{-1 - i\sqrt{23}}{4} \right\} \]